2013
DOI: 10.1016/j.jpolmod.2013.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The impact of democracy and press freedom on corruption: Conditionality matters

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 36 publications
5
49
0
1
Order By: Relevance
“…However, firms in which the control rights are handled and managed by government officials through regulation are required to pay bribe or else exit from the market. In some of the recent studies, Goel and Nelson (2010) and Kalenborna and Lessmann (2013) have also found that type and size of government institutions are crucial factors for the level of corruption.…”
Section: Theoretical and Empirical Hypothesesmentioning
confidence: 99%
“…However, firms in which the control rights are handled and managed by government officials through regulation are required to pay bribe or else exit from the market. In some of the recent studies, Goel and Nelson (2010) and Kalenborna and Lessmann (2013) have also found that type and size of government institutions are crucial factors for the level of corruption.…”
Section: Theoretical and Empirical Hypothesesmentioning
confidence: 99%
“…Research on the causes, consequences and combat strategies of corruption are manifold and very revealing. Previous studies indicate, for example, that wellestablished democracies show lower levels of corruption than authoritarian regimes or young democracies [3][4][5][6]. At the same time, high levels of corruption undermine democracy.…”
mentioning
confidence: 99%
“…However, various studies have established empirically that press freedom and democracy together have a significant impact on controlling corruption (Chowdhury, 2004, Bhattacharyya andHodler, 2012, as well as Kalenborn and Lessmann 2013). The emphasis here is on the finding that democracy and press freedom develop their positive impact jointly -they are complements in the fight against corruption, not substitutes.…”
Section: A Do Voters Really Punish Corrupt Politicians?mentioning
confidence: 94%